Mobile proximity discovery service - Sun, Bo. (2010)
This report is a summary of the author’s Final Year Project in School of EEE, Info-communications Engineering division. The purpose of the FYP is to provide students with the opportunity to showcase the abilities and talents they have acquired during their time at SCI. Final year students from Nanyang Technological University are subjected to this mandatory module and are attached to supervisors and professors from either their school of study or local companies. During his six-month study with regard to the project, the author was attached to EEE3 - ICIS Practicum Lab (Loc S2-B3a-01). Under the guidance of his supervisor and colleagues, the author was able to pick up adequate engineering knowledge and learnt from website and the engineers at the forefront of the R&D sector of the information & communication technology. This report first gives an introduction to the project background and objectives. It will be followed by the detailed breakdown of the literature review the author has gone through and the key technologies he has reviewed during his project period. It also includes the main sub-modules he had undertaken, which encompasses everything he has learnt throughout in order to complete the project. The author will focus on two most inspiring modules that consist of the whole project. 1. Software Development – Wi-Fi Radar (MAC address + signal strength) 2. Software Application – Real device implementation Finally, the report closes with the summary of the learning experience of the author throughout this program and how he has learnt from this experience. Some modules of the projects are still working in progress till the date of submission of this report.